Composition of exosomes derived from Atlantic salmon (Salmo salar) head kidney leukocytes - Strandskog, Guro; Sobhkhez, Mehrdad; Jørgensen, Jorunn B; Iliev, Dimitar Borisov (ISDCI, Murcia, 2015)
Exosomes are secreted nanosize vesicles (30−100 nm) derived from multivesicular endosomes. Exosomes are released by different immune cell types, including T- and B-lymphocytes, mast cells and antigen-presenting cells (APCs). The composition of exosomes - including protein and RNA content reflects their endosomal origin and the type of cells that produce them. Mammalian APCs produce large amounts of exosomes loaded with MHC class I and II molecules with important immunomodulatory properties. In the current study, exosomes were isolated from salmon head kidney leukocytes stimulated with CpG oligonucleotides and yeast beta-glucan (BG) and their protein composition was studied using Western blotting and LC-MS/MS analysis. Major exosome markers were detected including flotillin, CD63, CD81, CD9 and MHC-I and II molecules. Ontology analysis indicated that the exosome samples were enriched in ribosomal, membrane-associated as well as nuclear proteins the last of which reflects the abundance of histones within exosome preparations. Interestingly, label-free MS quantitation suggests that the exosomes might be derived from cross-presenting compartments as they are also enriched in proteins involved in trafficking and loading of MHC-I with exogenous antigens.